Combining On‐Chip Synthesis of a Focused Combinatorial Library with Computational Target Prediction Reveals Imidazopyridine GPCR Ligands1. Issue 2 (26th November 2013) - Reutlinger, Michael; Rodrigues, Tiago; Schneider, Petra; Schneider, Gisbert
Abstract Using the example of the Ugi three‐component reaction we report a fast and efficient microfluidic‐assisted entry into the imidazopyridine scaffold, where building block prioritization was coupled to a new computational method for predicting ligand–target associations. We identified an innovative GPCR‐modulating combinatorial chemotype featuring ligand‐efficient adenosine A1/2B and adrenergic α1A/B receptor antagonists. Our results suggest the tight integration of microfluidics‐assisted synthesis with computer‐based target prediction as a viable approach to rapidly generate bioactivity‐focused combinatorial compound libraries with high success rates.